Diversity and Language Teaching: Theoretical Reflections and Practical Approaches for Inclusive Education - Aquino, Marceli (Debates em Educação, 2025)
In this article we discuss the importance of diversity and criticality in foreign language teaching, with an emphasis on teacher education and textbook analysis. Based on Critical Applied Linguistics (Pennycook, 2001), Critical Pedagogy (Freire, 1997), and decolonial perspectives, we present the outcome of a workshop held with professors from the University of São Paulo (USP) and the University of Augsburg. The workshop explored the challenges and possibilities of making language education more representative, inclusive, and sensitive to local realities. Topics such as family and gender representations in textbooks, inclusive language, and the treatment of traditionally avoided subjects (such as politics, religion, and sexual identity) were addressed. Based on this experience, the article proposes pedagogical strategies focused on critical analysis of materials, the usage of diverse types of media, and the development of active listening practices that embrace different identities. It concludes that socially engaged language teaching should value the plural voices of learners and educators, fostering a more transformative learning environment.